Improving Quality of Islamic Education Through Community Based Education: Principal Engagement - Arbi, Arbi (Jurnal Pendidikan Islam, 2018)
The emergence of a community-based education paradigm is triggered by a large flow of modernization and democratization. Education should be decentralized. Its implementation in schools should be collaborative, and the principal has a big hand in this. Therefore, this study aims to examine the involvement or participation of the principal in improving the quality of Islamic Religious Education (PAI) community-based in junior high school. The data are collected through in-depth interviews, observations, literature studies and documentation instruments. This study Â shows that the principal's concern on religious affairs and the improvement of the quality of PAI learning is relatively high. This can be seen from his programs conducting recitation Â Â on Islamic and national holidays, Dhuha studies, tahfidz one day one verse, book of yaumi and verse book, tajwid learning Â Â or tahsin for teachers, qurban animal repayment Â Â and highly motivating teachers to have skills, develop existing curriculum, and improve the competence of teaching based on social piety.